A Systematic Review on the Research Progress and Evolving Trends of Occupational Health and Safety Management: A Bibliometric Analysis of Mapping Knowledge Domains - Wang, Yujie; Chen, Hong; Liu, Bei; Yang, Menghua; Long, Qianyi (Frontiers in Public Health, 2020)
Background: Effective occupational health and safety management (OHSM) is important to employee health, enterprise sustainability, and social stability. However, scientific research into OHSM lags behind practice, and contextualizing OHSM research from the perspective of its historical evolution is urgently required. Methods: The mapping of knowledge domains, based on bibliometric analysis, was adopted to classify 4,852 journal articles related to OHSM listed in the core database of Web of Science and published between 1900 and 2018. Results and Conclusions: Risk assessment/management at the organizational level were found to have always been research hotspots, and the relationship between safety culture/atmosphere, sickness absence, and safety performance, among other factors, have become core research topics in the field in recent years. Research at the individual level has gradually evolved from an early focus on physiological problems such as work-related musculoskeletal disorders and low back pain, further toward issues such as occupational stress, mental health, and quality of life. In addition, the results of clustering analysis based on high-frequency keywords indicated six aspects of OHSM: OHSM mode and method; OHSM systems and standards; OHS risk assessment and management; OHSM and safety culture; mental health and quality of life; and specific disease management. Future development trends in OHSM research are described providing theoretical and practical reference for further study.